Examining animal health and production in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Livestock production and diseases in the tropics: proceedings of the sixth international conference of institutes for tropical veterinary medicine,